Numerical simulation of aerodynamic interference between ejected payload and the parent aircraft - Leonid V Bykov; Oleg A Pashkov; Mikhail N Pravidlo; Dmitry S Yanyshev (RUDN Journal of Engineering Research, 2018)
The purpose of this paper is to develop reliable methodology for numerical modeling of the interference between parent aircraft and ejectable payload and to investigate the influence of the interference on aerodynamic characteristics of the payload. An appropriate algorithm for the said problem is proposed. A mathematical model for supersonic flow around a solid body as well as its finite volume discretization process is described. In the presented mathematical model, a turbulence model is added to the Navier-Stokes system of equations. Namely, Menter’s SST model was chosen. Coupled solver algorithm is reviewed. Implicit Euler scheme is used for time discretization and Newton’s method is implemented to linearize the system of equations. The specifics of determining the appropriate boundary conditions and nondimensionalization of the aerodynamic coefficients are described. The calculations for the isolated payload were performed on an unstructured grid with 9 million cells and for the payload interfered by the parent aircraft - on a 24 million grid. As a result, the summarized aerodynamic characteristics for the payload were obtained for the isolated payload as well as for the payload in presence of the parent aircraft. The characteristics of the isolated object are compared with the ones of the object in presence of the parent aircraft in two different positions - Y rel = 0 m and Y rel = 0.6 m. The developed method was verified using wind tunnel data. It was identified that in presence of the parent aircraft, the coefficients of normal and side force are not zero as opposed to the isolated payload. Moving away from the parent aircraft decreases the interference and thus the side force, as well as the pitch and yaw torques. The obtained results show that the proposed method could be used in other cases of aerodynamic interference between moving objects.